Promoting self-reflection over re-teaching: Addressing students’ misconceptions with ‘my favorite no’ - Joanne Caniglia (JME (Journal of Mathematics Education), 2020)
Misconceptions are an important aspect of learning and teaching mathematics. What are effective ways for teachers to confront misconceptions and prevent their reoccurrence?  This mixed-methods study examined instrumental and conceptual understandings of students’ errors, mistakes, and misconceptions in a 7th grade mathematics classroom utilizing the ‘My Favorite No’ strategy. Fifty-five students from a Midwest middle school were divided into two groups with similar abilities, with one group confronting misconceptions using the ‘My Favorite No” strategy while the other group received information about a potential error directly from a teacher.  A brief survey of questions followed for students in the “My Favorite No’ class. One group was concerned with conceptual understanding and making connections, and able to solve similar problems.  In the second group, students improved from pretests, yet did not improve as much as students using ‘My Favorite No.’ Thus, teachers are encouraged to consider using “My Favorite No” a strategy where students are in an environment in which they discover their errors and believe in the value of making a mistake.